STUDENTS’ PERCEPTION ON THE USE OF BRITISH COUNCIL ENGLISHSCORE IN HIGHER EDUCATION - Parnawati, Tantry Ajeng; Ulinuha, Atik (Universitas Tribhuwana Tunggadewi, 2024)
This study investigates higher education students’ perceptions and experiences with the British Council EnglishScore (BCES) test as part of their graduation requirements. To achieve this objective, a descriptive quantitative approach was employed, incorporating case study analysis. Data were collected through an online questionnaire, interviews, and observations. The questionnaire data were analyzed quantitatively using SPSS for simple percentage analysis.The findings revealed that 84.6% of participants had no prior experience learning English outside the classroom, and 68.1% had not taken any English proficiency test. However, 47.3% of students strongly agreed with using BCES as a graduation requirement. Regarding BCES as an e-application for assessing English proficiency, 40.7% of participants felt comfortable using it, and 44% strongly agreed that the language used in the test reflects real-life usage. Additionally, 46.2% of participants felt ready to take the test, 39.6% felt challenged, and 45.1% felt focused. Furthermore, 39.6% strongly agreed that BCES motivated them to read more English material.Future studies could explore the impact of BCES on students' language proficiency and overall academic performance.